Interferon lambda in respiratory viral infection: immunomodulatory functions and antiviral effects in epithelium - Liu, Yong-Guang; Jin, Su-Wei; Zhang, Shan-Shan; Xia, Tian-Ji; Liao, Yong-Hong; Pan, Rui-Le; Yan, Ming-Zhu; Chang, Qi (Frontiers in Immunology, 2024)
Type III interferon (IFN-λ), a new member of the IFN family, was initially considered to possess antiviral functions similar to those of type I interferon, both of which are induced via the JAK/STAT pathway. Nevertheless, recent findings demonstrated that IFN-λ exerts a nonredundant antiviral function at the mucosal surface, preferentially produced in epithelial cells in contrast to type I interferon, and its function cannot be replaced by type I interferon. This review summarizes recent studies showing that IFN-λ inhibits the spread of viruses from the cell surface to the body. Further studies have found that the role of IFN-λ is not only limited to the abovementioned functions, but it can also can exert direct and/or indirect effects on immune cells in virus-induced inflammation. This review focuses on the antiviral activity of IFN-λ in the mucosal epithelial cells and its action on immune cells and summarizes the pathways by which IFN-λ exerts its action and differentiates it from other interferons in terms of mechanism. Finally, we conclude that IFN-λ is a potent epidermal antiviral factor that enhances the respiratory mucosal immune response and has excellent therapeutic potential in combating respiratory viral infections.